PENGARUH KONTRASEPSI HORMONAL TERHADAP KESEHATAN WANITA - Anjani, Dewi (Jurnal Kesehatan, 2024)
This study aims to evaluate the effects of hormonal contraception use, particularly oral contraceptive pills (OCPs), on the physical and mental health of women. Data were collected through questionnaire surveys and in-depth interviews with respondents who use OCPs and those who do not use hormonal contraception. The results indicate that OCPs can provide benefits in regulating menstrual cycles and preventing unintended pregnancies, but they can also cause side effects such as mood changes, decreased libido, and health risks such as blood clotting. It is important for women to consider the benefits and risks associated with OCP use and to consult with a doctor before deciding to initiate or discontinue use. Further studies are needed to better understand the long-term effects of OCP use and potential associated health risks.